Home and non-home based childhood accidental injury in Hospital Universiti Sains Malaysia - Hussain, Aminath Minna (2014)
Accidental injury causes significant morbidity and mortality in children but limited data is available in our local set up. The aim of this study was to explore the characteristics of accidental injury in children who sought treatment at the Accident and Emergency (A&E) of Hospital Universiti Sains Malaysia (HUSM) and to determine the associated risk factors for home-based accidental injury in comparison to non-home based accidental injury. METHOD A prospective cross-sectional study was done for 5 months duration. A standard data collection form was used to collect the sociodemographic character of injury and possible risk factors related to injury. The accidental injuries were classified according to the 10th revision of International Statistical Classification of Diseases and Related Health Problems (ICD-10). RESULTS There were 380 children included in the study from December 2013 till April 2014. All types of accidental injuries except motor vehicle accidents (MVA) occurred more often at home than outside. Falls were the most common accidental injury. The majority of home-based accidents occurred in the youngest age group. Males were more commonly involved with home-based accidental injuries and the ratio of male to female was 1.9:1. Smaller families and being the first three children in the family have higher percentages of home-based accidental injury. Father’s occupation as an executive position and mother being a house wife led to more home-based accidental injuries. Family income being in the range of RM1000-3000/ month was involved with more home-based accidents. Father, mother and child’s carers having a degree level of education were in majority involved with home-based accidental injuries. Most of the home accidental injuries had transient disabilities and did not require admission. CONCLUSION Majority of the childhood injuries were home-based accidental injuries. Falls were the most common accidental injury although burns, bites and stings were the most common home-based accidental injury. Boys were more involved with accidental injury in both home-based as well as non-home based. Three risk factors the age of the child, that being the younger age groups, all types of accidental injuries except motor vehicle accidents and parents as the carer were found to be significantly associated with home-based accidental injury in comparison to non-home based accidental injury. In the presence of these three factors the risk for home- based accidental injury could be predicted with an accuracy of 87.6%.